THE EFFECT OF NEUROLOGICAL IMPRESS METHOD UPON READING COMPREHENSION ACHIEVEMENT OF TENTH GRADE STUDENTS OF SMA PGRI 6 DENPASAR IN ACADEMIC YEAR 2016/2017 - YUNIARI, NI MADE (Widya Accarya, 2016)
AbstractThis research aimed at investigating whether or not there was any significant effect of Neurological Impress Method upon Reading Comprehension Achievement of Tenth Grade Students of SMA PGRI 6 Denpasar in Academic Year 2016/2017. On the basis of the purpose of the research, there was a null hypothesis formulated. The sampling technique used in this research was cluster random sampling. Two classes: X IPS 1 and X IPS 2 were selected as the samples of research. Class X IPS 1 was selected as the experimental group and X IPS 2 was selected as the control group. Each class consists of 41 students. In this research, the data were obtained by conducting reading comprehension test: normality and homogeneity test, try-out test, and posttest. The obtain data were analyzed through descriptive and inferential statistics. From the descriptive analysis, it was found out that the mean score for the group using Neurological Impress Method was 7.78 while the group using Conventional Reading technique was 7.18. It means that Neurological Impress Method was better than Conventional Reading technique.Â  The result of inferential statistic shows that to (2.13) more than tcv (1.98). The null hypothesis which states there is significant effect of studentsâ?? reading comprehension achievement between the two groups was rejected.Keywords: Effect, Neurological Impress Method (NIM), Reading Comprehension, AchievementÂ AbstrakPenelitian ini bertujuan untuk menginvestigasi apakah ada pengaruh yang signifikan dari Neurological Impress Method terhadap pencapaian pemahaman membaca siswa kelas 10 SMA PGRI 6 Denpasar tahun akademik 2016/2017. Berdasarkan tujuan penelitian tersubut, hipotesis null diformulasikan. Teknik sampel yang digunakan di penelitian ini adalah cluster random sampling. Ada dua kelas yaitu X IPS 1 dan XIPS 2 yang dipilih sebagai sampel penelitian. Kelas X IPS 1 dipilih sebagai grup eksperimen and kelas X IPS 2 sebagai grup kontrol. Setiap kelas terdiri dari 41 orang siswa. Pada penelitian ini, data diperoleh dari melaksanakan tes pemahaman membaca : normality dan homogeneity test, try-out test, dan posttest. Data tersebut kemudian dianalisa melalui descriptive dan inferential statistics. Dari analisis deskriptif ditemukan bahwa skor mean dari grup yg memakai Neurological Impress Method adalah 7.78, sedangkan skor mean dari grup yang menakai teknik membaca konvensional adalah 7.18. Itu berarti Neurological Impress Method lebih baik daripada teknik membaca konvensional. Kemudian hasil dari inferential statistics menunjukkan bahwa to (2.13) lebih besar dari tcv dua grup tersebut dinyatakan ditolak.Kata Kunci: Pengaruh, Effect, Neurological Impress Method (NIM), Pemahaman Membaca, PencapaianÂ Â Â Â Â Â Â Â (1.98). Sehingga null hipotesis yang menyebutkan bahwa ada pengaruh signifikan dari pencapaian pemahaman membaca siswa Antara